2012
DOI: 10.3389/fimmu.2012.00056
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 Contributes to Control of Chronic Helicobacter Pylori Infection and the Development of T Helper Responses in a Mouse Model1

Abstract: The immune response to Helicobacter pylori involves a mixed T helper-1, T helper-2, and T helper-17 response. It has been suggested that T helper cells contribute to the gastric inflammatory response during infection, and that T helper 1 (Th1) and T helper 17 (Th17) subsets may be required for control of H. pylori colonization in the stomach. The relative contributions of these subsets to gastritis and control of infection are still under investigation. IL-23 plays a role in stabilizing and expanding Th17 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 52 publications
4
34
0
Order By: Relevance
“…The NAbs generated by B-1 cells bind to self-antigens such as oxidized lipids [37,38] and new antigens on apoptotic cells [39]. An increased incidence of autoimmune disorder occurs in gene-targeted mice that lack secreted IgMs.…”
Section: Self-reactive B Lymphocytes and Production Of Nabsmentioning
confidence: 99%
“…The NAbs generated by B-1 cells bind to self-antigens such as oxidized lipids [37,38] and new antigens on apoptotic cells [39]. An increased incidence of autoimmune disorder occurs in gene-targeted mice that lack secreted IgMs.…”
Section: Self-reactive B Lymphocytes and Production Of Nabsmentioning
confidence: 99%
“…IL-17 is present in biopsies of H. pylori -infected patients and mice, suggesting that IL-17 contributes to Helicobacter-associated pathology[21], [22], [23]. Two recent studies employing the IL-23 p19 KO mouse model have demonstrated a reduction in gastric pathology compared to wild type mice during chronic H. pylori infection[24], [25]. Our own observations demonstrate a significant increase of IL-17 following challenge of immunized mice, and a strong Th17 recall response in the T cells from immunized mice[10].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the role of IFN-γ in promoting inflammation is well established through the studies carried out in gene knockout mice, the role of IL-17 in promoting inflammation is less clear. Studies in mice lacking IL-17 (IL-17A −/− /IL-23p19 −/− ) report a dampened inflammation and reduced neutrophil infiltration during chronic H. pylori infection compared to wild-type mice, suggesting that IL-17 could promote inflammation through neutrophil recruitment (Shi et al, 2010;Horvath et al, 2012;Shiomi et al, 2008). Comprehensive studies of the IFN-γ and IL-17 levels in the stomach and the relation of these cytokines to inflammation and disease are currently lacking.…”
Section: Whether B Cells Have Similar Immune-regulatory Functions Imentioning
confidence: 97%